An unusual case of multiple oral pyogenic granuloma, ¿associated with treatment with levothyroxin? - Gutiérrez Patiño-Paul, Alejandro Arturo (2021)
Pyogenic Granuloma (GP) is a tumorous, non-neoplastic, vascular, generally solitary lesion that presents itself in the oral cavity or skin, the etiology is still not very clear, it is considered to be a reactive lesion to several low grade stimuli, among which we can count repeated trauma, aggressions, hormonal factors and certain drugs. The multiple GP, is a rare phenomenon, generally associated with the use of drugs, such as carbamacepine, cyclosporine, retinoids, levothyroxine, etc. It presents the case of a patient of 50 years, referred for presenting increased volume in alveolar ridge of the first, third and fourth quadrants, with a history of erythrodermic psoriasis and hypothyroidism, in treatment with levothyroxine approximately six months before the lesions occur; Surgical exeresis and subperiosteal curettage is performed, samples were sent to pathological anatomy, confirming the definitive diagnosis of GP; because of the history, and the almost simultaneous appearance of the lesions in multiple quadrants, it is suspected that these are associated with the therapeutic consumption of levothyroxine for hypothyroidism.